Composite anti-reflection film for 1550 nm wave band and preparation method thereof
Patent Information
- Application Number
- CN202611487578.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该方案存在以下不足:一方面,PECVD工艺的沉积速率较快,成膜过程为非自限制生长,膜层内部不可避免存在针孔、微裂纹等缺陷,致密性不足,导致膜层在长期使用过程中容易受环境因素影响而性能退化,同时膜层界面处的缺陷会增加光散射损耗;另一方面,PECVD的厚度控制精度有限,对于厚度在10nm以下的超薄界面层,沉积时间仅数秒至数十秒,工艺窗口极为狭窄,批次间重复性差
(1)本发明提供的复合减反增透膜采用CVD氮化硅层、ALD氮化硅层、CVD二氧化硅层和ALD二氧化硅层的四层膜系结构,通过高折射率氮化硅层与低折射率二氧化硅层的交替组合,利用多层干涉效应实现宽谱段减反增透。以1550nm为中心波长,在1400-1700nm波段范围内进行多目标优化确定各膜层厚度,可实现宽谱段范围内较低的反射率。
Smart Images

Figure CN122984101A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical thin film technology, and in particular to a composite antireflective and anti-reflective film for the 1550nm wavelength band and its preparation method. Background Technology
[0002] The 1550nm band is a core window for optical fiber communication, possessing the dual advantages of the lowest fiber transmission loss (approximately 0.2dB / km) and the flattest gain in erbium-doped fiber amplifiers, forming the physical basis for dense wavelength division multiplexing (DWDM) systems and coherent optical communication. Simultaneously, the 1550nm band is within the eye-safe band and is finding widespread application in automotive LiDAR and autonomous driving. In these applications, optical signals frequently traverse various optical interfaces such as semiconductor / air and glass / air. Uncoated interfaces exhibit strong Fresnel reflection, leading to a significant decrease in system light energy utilization. Therefore, high-performance anti-reflection and anti-reflection coatings are an indispensable key technology for 1550nm band optoelectronic devices.
[0003] Currently, the following technical solutions are mainly used for antireflection and anti-reflection coatings in the 1550nm band: (1) Single-layer antireflection coating. Single-layer silicon nitride is the most representative, which uses the interference effect of a single-layer film to achieve antireflection at a specific wavelength. This solution has a simple structure and low preparation cost, but it is limited by the dispersion characteristics of a single material and can only achieve the ideal antireflection effect in a narrow wavelength range. It is also extremely sensitive to film thickness deviation, which makes it difficult to meet the application requirements of modern optoelectronic devices for a wide spectrum and high stability. (2) Multilayer antireflection coating by full chemical vapor deposition (CVD). Plasma-enhanced chemical vapor deposition (PECVD) technology is used to alternately deposit silicon dioxide and silicon nitride multilayer films, which utilizes the multilayer interference effect to broaden the antireflection bandwidth. This is the mainstream technical route in the industry at present. However, this scheme has the following shortcomings: On the one hand, the deposition rate of PECVD process is relatively fast, and the film formation process is a non-self-limiting growth. Inevitably, there are defects such as pinholes and microcracks inside the film layer, resulting in insufficient density. This makes the film layer susceptible to environmental factors and performance degradation during long-term use. At the same time, defects at the film layer interface will increase light scattering loss. On the other hand, the thickness control precision of PECVD is limited. For ultrathin interface layers with a thickness of less than 10 nm, the deposition time is only a few seconds to tens of seconds, the process window is extremely narrow, and the batch repeatability is poor. (3) Atomic Layer Deposition (ALD) Multilayer Antireflection Film. By utilizing the self-limiting surface reaction characteristics of ALD technology, atomic-level thickness control and high film density can be achieved. However, the ALD deposition rate is extremely low. It takes thousands of deposition cycles to prepare a film system with a total thickness of hundreds of nanometers. The production efficiency is low and the equipment cost is high, which makes it difficult to meet the needs of large-scale industrial mass production.
[0004] Furthermore, in the aforementioned CVD or ALD multilayer film systems, differences in thermal expansion coefficients and intrinsic stress exist between different materials and even between the same material prepared using different processes. This can easily lead to stress mismatch between film layers, affecting film adhesion and long-term reliability. Meanwhile, existing antireflective film designs for the 1550nm band mostly employ simple bilayer or trilayer structures, failing to fully utilize the optical interference effect of multilayer films to achieve superior broadband antireflective performance. They also lack systematic film system optimization and precise parameter matching specifically for the optical characteristics of the 1550nm band.
[0005] In summary, existing antireflective coatings for the 1550nm band still have certain limitations in terms of film density, broadband antireflective performance, interlayer stress matching, and precise control of ultrathin layers. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the prior art by providing a composite antireflection and anti-reflection film for the 1550nm band and its preparation method. By combining CVD and ALD processes, a four-layer composite film system—a CVD silicon nitride layer, an ALD silicon nitride layer, a CVD silicon dioxide layer, and an ALD silicon dioxide layer—is sequentially formed on the surface of an optical substrate to obtain a composite antireflection and anti-reflection film with excellent broadband antireflection performance and high film density.
[0007] To achieve the above objectives, the present invention provides a composite antireflection and anti-reflection coating for the 1550nm band, disposed on the surface of an optical substrate, wherein the composite antireflection and anti-reflection coating comprises the following layers stacked sequentially from the substrate outward: CVD silicon nitride layer, ALD silicon nitride layer, CVD silicon dioxide layer, ALD silicon dioxide layer.
[0008] In some optional embodiments, the thickness of the CVD silicon nitride layer is 100-150 nm, the thickness of the ALD silicon nitride layer is 1-10 nm, the thickness of the CVD silicon dioxide layer is 250-350 nm, and the thickness of the ALD silicon dioxide layer is 1-10 nm.
[0009] In some optional embodiments, the thickness of the CVD silicon nitride layer is 116 nm, the thickness of the ALD silicon nitride layer is 5 nm, the thickness of the CVD silicon dioxide layer is 314 nm, and the thickness of the ALD silicon dioxide layer is 5 nm.
[0010] The CVD silicon nitride layer is prepared using plasma-enhanced chemical vapor deposition (PECVD). Silicon nitride has a refractive index of 1.8-2.0 in the 1550nm wavelength range, classifying it as a high-refractive-index material. The specified thickness allows this layer to provide phase modulation at a quarter-wavelength optical thickness in the 1550nm wavelength range, achieving destructive interference of reflected light together with the subsequent low-refractive-index layer. This layer, as the bottom layer, directly contacts the optical substrate, providing adhesion.
[0011] The ALD silicon nitride layer is fabricated using atomic layer deposition (ALD) technology, leveraging the self-limiting surface reaction characteristics of ALD to achieve atomic-level thickness control. This ultrathin layer serves as an interface buffer between the CVD silicon nitride layer and the CVD silicon dioxide layer. Through the layer-by-layer growth mode of ALD, a dense, pinhole-free transition interface is formed, improving the interface quality of the heteromaterials. Simultaneously, its ultrathin thickness allows for precise control over its impact on the overall optical performance of the film system without affecting the optical interference design of the main film system. The ALD silicon nitride layer exhibits higher density and lower defect density than the CVD silicon nitride layer, preventing pinholes present in the CVD silicon nitride layer from propagating into subsequent film layers.
[0012] The CVD silica layer was prepared using plasma-enhanced chemical vapor deposition (PECVD). Silica has a refractive index of 1.4-1.5 in the 1550 nm wavelength range, classifying it as a low-refractive-index material. The specified thickness allows the layer to provide phase modulation at approximately three-quarters of its optical thickness in the 1550 nm wavelength range.
[0013] The ALD silica layer was prepared using atomic layer deposition technology.
[0014] The thickness combination of the above-mentioned film layers is optimized based on the McLeod optical thin film design theory: the reflectivity of the multilayer film system is calculated by the characteristic matrix method, and multi-objective optimization is carried out in the 1400-1700nm band with 1550nm as the center wavelength to determine the thickness combination of each film layer.
[0015] The present invention also provides a method for preparing the composite antireflection and antireflection film for the 1550nm band, comprising the following steps: S1. A CVD silicon nitride layer is deposited on the surface of an optical substrate using a plasma-enhanced chemical vapor deposition process; S2. An ALD silicon nitride layer is deposited on the surface of the CVD silicon nitride layer using an atomic layer deposition process; S3. A CVD silicon dioxide layer is deposited on the surface of the ALD silicon nitride layer using a plasma-enhanced chemical vapor deposition process; S4. An ALD silicon dioxide layer is deposited on the surface of the CVD silicon dioxide layer using an atomic layer deposition process to obtain the composite antireflection and anti-reflection film for the 1550nm band.
[0016] In some alternative embodiments, S1 further includes pre-cleaning the optical substrate before depositing the CVD silicon nitride layer: cleaning the substrate surface with deionized water to remove impurities; subsequently immersing the substrate surface in ethanol and acetone; and drying the substrate after cleaning to remove surface chemical contaminants.
[0017] In some optional embodiments, in S1, the conditions for depositing the CVD silicon nitride layer are: trimethylsilylamine and nitrogen as reaction gases, substrate temperature of 250-350°C, and radio frequency power of 800-1200W.
[0018] In some optional embodiments, in S2, the conditions for depositing the ALD silicon nitride layer are as follows: the chamber is evacuated to 0-20 Pa, trimethylsilylamine is used as the silicon precursor, nitrogen plasma is used as the nitrogen source, the deposition temperature is 250-350°C, and a single ALD cycle includes sequential pulsed silicon precursor, purging, nitrogen plasma treatment and purging, and the cycle is repeated 40-80 times.
[0019] In some optional embodiments, in S3, the conditions for depositing the CVD silicon dioxide layer are: evacuating the chamber to 0-20 Pa, using diisopropylaminosilane and oxygen as reaction gases, a substrate temperature of 250-350 °C, and a radio frequency power of 1200-1800 W.
[0020] In some optional embodiments, in S4, the conditions for depositing the ALD silicon dioxide layer are as follows: the chamber is evacuated to 0-20 Pa, diisopropylaminosilane is used as the silicon precursor, oxygen plasma is used as the oxygen source, the deposition temperature is 250-350°C, and a single ALD cycle includes sequential pulsed silicon precursor, purging, oxygen plasma treatment and purging, and the cycle is repeated 30-50 times.
[0021] In some alternative implementations, the depositions in S1 to S4 are completed continuously in the same vacuum reaction chamber by switching between in-situ atomic layer deposition and plasma-enhanced chemical vapor deposition.
[0022] In some optional embodiments, S4 further includes annealing the deposited film; the annealing is performed under a nitrogen atmosphere; the annealing temperature is 250-350°C and the time is 5-15 min, which is used to eliminate internal stress and interface defects in the film and promote film densification.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite antireflection and anti-reflection coating provided by this invention adopts a four-layer film structure consisting of a CVD silicon nitride layer, an ALD silicon nitride layer, a CVD silicon dioxide layer, and an ALD silicon dioxide layer. By alternating the combination of high-refractive-index silicon nitride layers and low-refractive-index silicon dioxide layers, a wide-spectrum antireflection and anti-reflection effect is achieved using multi-layer interference. With 1550nm as the center wavelength, multi-objective optimization is performed in the 1400-1700nm band to determine the thickness of each film layer, which can achieve a low reflectivity in a wide spectral range.
[0024] (2) In this invention, an ALD silicon nitride layer is set between the CVD silicon nitride layer and the CVD silicon dioxide layer. This ultrathin layer forms a dense, pinhole-free transition interface through a layer-by-layer growth mode of atomic layer deposition, which can improve the interface quality of heterogeneous materials. At the same time, the influence of this ultrathin layer on the overall optical performance of the film system can be controlled, and it does not affect the optical interference design of the main film system. The ALD silicon nitride layer has higher density and lower defect density than the CVD silicon nitride layer, which can prevent the pinholes present in the CVD silicon nitride layer from extending to subsequent film layers.
[0025] (3) In this invention, an ALD silicon dioxide layer is set on the CVD silicon dioxide layer. This ultrathin layer forms a dense, pinhole-free surface layer through atomic layer deposition, which can form a conformal coverage of nanoscale defects on the surface of the CVD silicon dioxide layer, thereby achieving a good surface sealing effect.
[0026] (4) The preparation method of the present invention uses CVD process to prepare silicon nitride layer and silicon dioxide layer as the main film layer, which ensures high preparation efficiency. At the same time, ALD process is used to prepare ultrathin interface layer and ultrathin surface layer, which ensures film density and thickness control accuracy. The combination of CVD process and ALD process is beneficial to balance preparation efficiency and film quality.
[0027] (5) In the preferred preparation method of the present invention, the deposition of each film layer is completed continuously in the same vacuum reaction chamber by switching between ALD and CVD processes in situ. There is no need to break the vacuum or transfer the substrate between each film layer, which helps to avoid particulate pollution and natural oxide layer formation caused by atmospheric exposure and improves the purity of the interface between film layers. At the same time, it helps to reduce the loading, alignment and heating waiting time between processes and improve the preparation efficiency.
[0028] In summary, the composite antireflection and anti-reflection film provided by this invention has the characteristics of excellent antireflection performance over a wide spectrum, high film density, good interface quality, high reliability, and high preparation efficiency, and is suitable for optoelectronic devices in the 1550nm band. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the composite antireflection and antireflection film used in the 1550nm band in Embodiment 1 of the present invention; Figure 2This is a SEM characterization image of the CVD silicon dioxide layer in Embodiment 1 of the present invention; Figure 3 This is a SEM characterization image of the ALD silicon dioxide layer in Embodiment 1 of the present invention; Figure 4 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in the wavelength range of 1400-1700nm in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in the wavelength range of 1500-1600nm in Embodiment 1 of the present invention; Figure 6 This is a schematic diagram of the reflectance of the composite antireflection and antireflection film in Comparative Example 1 of the present invention in the wavelength range of 1400-1700nm; Figure 7 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 1 of the present invention in the wavelength range of 1500-1600nm; Figure 8 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 2 of the present invention in the wavelength range of 1400-1700nm; Figure 9 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 2 of the present invention in the wavelength range of 1500-1600nm; Figure 10 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 3 of the present invention in the wavelength range of 1400-1700nm; Figure 11 This is a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 3 of the present invention in the wavelength range of 1500-1600nm. Detailed Implementation
[0030] The following embodiments are provided to better understand the present invention and are not limited to the described embodiments. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0031] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0032] Example 1.
[0033] This embodiment provides a method for preparing a composite antireflection and antireflection coating for the 1550nm band, including the following steps: Pre-cleaning of the optical glass substrate: The substrate surface is cleaned with deionized water to remove impurities; then the substrate surface is soaked and cleaned with ethanol and acetone; after cleaning, it is dried to remove surface chemical contaminants.
[0034] The pretreated optical glass substrate was placed in a plasma-enhanced chemical vapor deposition (PECVD) apparatus, and a CVD silicon nitride layer with a thickness of 116 nm was obtained by using trimethylsilylamine and nitrogen as reaction gases and depositing for 86 seconds at a substrate temperature of 300°C and an RF power of 1000W.
[0035] The chamber was evacuated to 10 Pa. Atomic layer deposition (ALD) was performed using trimethylsilylamine as the silicon precursor and nitrogen plasma as the nitrogen source at a deposition temperature of 300 °C. A single ALD cycle consisted of sequential pulsed trimethylsilylamine treatment (1 second), purging (12 seconds), nitrogen plasma treatment (10 seconds), and purging (10 seconds). The cycle was repeated 41 times to obtain an ALD silicon nitride layer with a thickness of 5 nm.
[0036] The chamber was evacuated to 10 Pa. Using diisopropylaminosilane and oxygen as reactants, a CVD silicon dioxide layer with a thickness of 314 nm was deposited for 245 seconds at a substrate temperature of 300 °C and an RF power of 1500 W.
[0037] The chamber was evacuated to 10 Pa. Atomic layer deposition (ALD) was performed using diisopropylaminosilane as the silicon precursor and oxygen plasma as the oxygen source at a deposition temperature of 300 °C. A single ALD cycle consisted of sequential pulsed diisopropylaminosilane (1 second), purging (12 seconds), oxygen plasma treatment (10 seconds), and purging (10 seconds). The cycle was repeated 38 times to obtain an ALD silicon dioxide layer with a thickness of 5 nm.
[0038] All of the above deposition steps are completed continuously in the same vacuum reaction chamber by switching between in-situ atomic layer deposition and plasma-enhanced chemical vapor deposition.
[0039] The optical glass substrate with all film layers deposited was annealed at 300°C for 10 min in a nitrogen atmosphere to obtain a composite antireflection and anti-reflection film for the 1550nm band.
[0040] A schematic diagram of the composite antireflection and antireflection coating used in the 1550nm band in Example 1 is shown below. Figure 1 As shown.
[0041] Example 2.
[0042] This embodiment provides a method for preparing a composite antireflection and antireflection film for the 1550nm band. The only difference from Embodiment 1 is that the thickness of the CVD silicon nitride layer is adjusted to 121nm (correspondingly, the deposition time is adjusted to 89 seconds), and the thickness of the CVD silicon dioxide layer is 319nm (correspondingly, the deposition time is adjusted to 249 seconds).
[0043] The remaining steps and conditions are the same as in Example 1.
[0044] Comparative Example 1.
[0045] This comparative example provides a composite antireflection and antireflection film, which differs from Example 1 only in that: the deposition of the ALD silicon nitride layer and the ALD silicon dioxide layer is omitted, the thickness of the CVD silicon nitride layer is adjusted to 121 nm (correspondingly, the deposition time is adjusted to 89 seconds), and the thickness of the CVD silicon dioxide layer is 319 nm (correspondingly, the deposition time is adjusted to 249 seconds).
[0046] The remaining steps and conditions are the same as in Example 1.
[0047] Comparative Example 2.
[0048] This comparative example provides a composite antireflection and antireflection membrane, in which all membrane layers are fabricated using plasma-enhanced chemical vapor deposition (PECVD) and consist of the following layers stacked sequentially from the substrate outwards: CVD silicon nitride layer (60nm, deposition time 44 seconds), CVD silicon dioxide layer (160nm, deposition time 125 seconds), CVD silicon nitride layer (60nm, deposition time 44 seconds), CVD silicon dioxide layer (160nm, deposition time 125 seconds).
[0049] The deposition process and conditions were the same as in Example 1.
[0050] Comparative Example 3.
[0051] This comparative example provides a composite antireflection and antireflection membrane, in which all layers are deposited using atomic layer deposition (ALD) technology, and the following layers are stacked sequentially from the substrate outwards: ALD silicon nitride layer (121nm, adjusted cycle count to 1000), ALD silicon dioxide layer (319nm, adjusted cycle count to 2454).
[0052] The deposition process and conditions were the same as in Example 1.
[0053] Experimental Example 1.
[0054] The surface morphology of the CVD silica layer and the ALD silica layer in Example 1 was observed using scanning electron microscopy (SEM). The SEM characterization image of the CVD silica layer in Example 1 is shown below. Figure 2As shown; SEM characterization image of the ALD silica layer in Example 1, as shown. Figure 3 As shown.
[0055] from Figure 2 It can be seen that the CVD silica layer surface has defects such as pinholes and microcracks, with high surface roughness, high defect density, and insufficient film density. From Figure 3 The results show that the ALD silica layer has a dense, smooth surface, free of defects such as pinholes and microcracks, and its defect density is significantly lower than that of the CVD silica layer. The ALD silica layer provides excellent conformal coverage for the nanoscale defects on the surface of the CVD silica layer.
[0056] Experimental Example 2.
[0057] The reflectance of the composite antireflection and antireflection films prepared in Example 1 and Comparative Examples 1-3 in the wavelength range of 1400-1700 nm was measured using a spectrophotometer with an incident angle of 0° (perpendicular incidence). A schematic diagram of the reflectance of the composite antireflection and antireflection film in Example 1 in the wavelength range of 1400-1700 nm is shown below. Figure 4 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Example 1 within the wavelength range of 1500-1600nm. Figure 5 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 1 in the wavelength range of 1400-1700nm. Figure 6 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 1 in the wavelength range of 1500-1600nm. Figure 7 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 2 in the wavelength range of 1400-1700nm. Figure 8 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 2 in the wavelength range of 1500-1600nm. Figure 9 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 3 in the wavelength range of 1400-1700nm. Figure 10 As shown; a schematic diagram of the reflectance of the composite antireflection and anti-reflection film in Comparative Example 3 in the wavelength range of 1500-1600nm. Figure 11 As shown.
[0058] from Figures 4-11As can be seen, the composite antireflective coating of Example 1 exhibits a reflectance of less than 0.9% in the 1400-1700nm broadband range, reaching its lowest value at 1550nm; within the key communication band of 1500-1600nm, the reflectance further decreases to below 0.1%, demonstrating excellent broadband antireflection performance. Comparative Example 1 shows a reflectance of no more than 6% in the 1400-1700nm range and 0.4-2.2% in the 1500-1600nm range, significantly higher than Example 1. Comparative Example 2 shows a reflectance of less than 2% in the 1400-1700nm range and less than 0.8% in the 1500-1600nm range, with its broadband antireflection effect significantly inferior to Example 1. Comparative Example 3 shows a reflectance of less than 1% in the 1400-1700nm range and less than 0.1% in the 1500-1600nm range, similar to the performance of Example 1. However, due to the self-limiting growth mechanism of ALD, its single cycle takes as long as 30-40 seconds, and the deposition rate is much lower than that of CVD process. The time required to prepare a film of the same thickness is several times to hundreds of times longer, which significantly increases the production cost and makes it difficult to meet the needs of industrial mass production.
[0059] Therefore, this invention, through the design of a four-layer composite film system consisting of a CVD silicon nitride layer, an ALD silicon nitride layer, a CVD silicon dioxide layer, and an ALD silicon dioxide layer, and the combined preparation of CVD and ALD processes, obtains a composite antireflection and antireflection film with excellent broadband antireflection performance, high film density, and good interface quality while ensuring high production efficiency. It is suitable for optoelectronic devices in the 1550nm band.
[0060] Finally, it should be noted that the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A composite antireflective coating for the 1550nm wavelength band, disposed on the surface of an optical substrate, characterized in that, The composite antireflective and anti-reflective membrane comprises the following layers stacked sequentially from the substrate outwards: CVD silicon nitride layer, ALD silicon nitride layer, CVD silicon dioxide layer, ALD silicon dioxide layer.
2. The composite antireflective and anti-reflective coating for the 1550nm band according to claim 1, characterized in that, The thickness of the CVD silicon nitride layer is 100-150 nm, the thickness of the ALD silicon nitride layer is 1-10 nm, the thickness of the CVD silicon dioxide layer is 250-350 nm, and the thickness of the ALD silicon dioxide layer is 1-10 nm.
3. The composite antireflective and anti-reflective coating for the 1550nm band according to claim 2, characterized in that, The thickness of the CVD silicon nitride layer is 116 nm, the thickness of the ALD silicon nitride layer is 5 nm, the thickness of the CVD silicon dioxide layer is 314 nm, and the thickness of the ALD silicon dioxide layer is 5 nm.
4. The method for preparing the composite antireflection and antireflection film for the 1550nm band according to any one of claims 1-3, characterized in that, Includes the following steps: S1. A CVD silicon nitride layer is deposited on the surface of an optical substrate using a plasma-enhanced chemical vapor deposition process; S2. An ALD silicon nitride layer is deposited on the surface of the CVD silicon nitride layer using an atomic layer deposition process; S3. A CVD silicon dioxide layer is deposited on the surface of the ALD silicon nitride layer using a plasma-enhanced chemical vapor deposition process; S4. An ALD silicon dioxide layer is deposited on the surface of the CVD silicon dioxide layer using an atomic layer deposition process to obtain the composite antireflection and anti-reflection film for the 1550nm band.
5. The preparation method according to claim 4, characterized in that, In S1, the conditions for depositing the CVD silicon nitride layer are: trimethylsilylamine and nitrogen as reaction gases, substrate temperature of 250-350℃, and radio frequency power of 800-1200W.
6. The preparation method according to claim 4, characterized in that, In S2, the conditions for depositing the ALD silicon nitride layer are as follows: trimethylsilylamine is used as the silicon precursor, nitrogen plasma is used as the nitrogen source, the deposition temperature is 250-350℃, and a single ALD cycle includes pulsed silicon precursor, purging, nitrogen plasma treatment and purging in sequence, and the cycle is repeated 40-80 times.
7. The preparation method according to claim 4, characterized in that, In S3, the conditions for depositing the CVD silicon dioxide layer are: using diisopropylaminosilane and oxygen as reaction gases, substrate temperature of 250-350℃, and radio frequency power of 1200-1800W.
8. The preparation method according to claim 4, characterized in that, In S4, the conditions for depositing the ALD silicon dioxide layer are as follows: using diisopropylaminosilane as the silicon precursor, using oxygen plasma as the oxygen source, the deposition temperature is 250-350℃, and a single ALD cycle includes sequential pulsed silicon precursor, purging, oxygen plasma treatment and purging, with the cycle repeated 30-50 times.
9. The preparation method according to claim 4, characterized in that, The depositions in S1 to S4 are continuously completed in the same vacuum reaction chamber by switching between in-situ atomic layer deposition and plasma-enhanced chemical vapor deposition.
10. The preparation method according to claim 4, characterized in that, S4 also includes annealing the deposited film; the annealing temperature is 250-350℃ and the time is 5-15min.